The identity of the non-orthodox population of Montenegro and religion - Jevtić Miroljub S. (Anali Pravnog Fakulteta u Beogradu)
This paper analyses the influence of religion on identity, especially the political identity and political behavior of the non-orthodox people of Montenegro. Goal of this paper is to show that non-orthodox minorities in Montenegro have a mass influence on the politics of this country. For example, without their votes, the independence of Montenegro would not be possible. This is very easy to calculate. 55% voted for the independence, and Muslims represents a little bit more than 19% of the Montenegro's population. All of them say they voted for the independence of Montenegro in 2006 referendum. Therefore, this political decision was highly dependent on the Muslim votes, and had a great influence on the Serbian interests. This fact should be highlighted. Moreover, one can say that this was one of the major defeats of Serbs in the last century. This paper shows that the identity of the Serbian speaking population of Montenegro is dependent on their religious background. Bosnians, Muslims, Montenegrin Muslims or Croats base their national identity on their Islamic or Roman Catholic confession. Moreover, this paper shows that the Albanian national question in Montenegro is a great example of how both Serbian science and politics failed to explain this issue. Serbian politicians and scientist are wrong in saying that Albanians are motivated only by antireligious nationalism in their actions, basing their attitude in complex Albanian society made of Muslims, Catholics and Orthodox Christians. Due to this fact religious aspect was completely ignored. However, a great number of Albanians fighting for Islamic State in Syria and Iraq are quite opposite to this attitude, and making Serbians to ask themselves - how is it possible that an atheist Albanians are fighting in the name of Islam? The situation is similar in Montenegro. In this paper we show that Albanians are also divided on religious lines and that this division has huge consequences. If Serbs has analyzed Albanians interreligious relations based on what we have in Montenegro, it would be easier for them to understand that Albanians failed to overcome their religious differences in the name of national unity, and consequently to understand why so many of them are fighting for ISIL. We also deal with the Croatian question in Montenegro. This paper will show that Montenegrin Croats are a part of the same Serbian body, like Bosnians or Muslims. They are divided from this body only because of their religious belonging to Roman Catholic religion. Under the pressure of the First Croat Catholic Congress in 1900 they accepted to declare as Croats as their national belonging. Prior to this, they were divided between the idea of Slavs and Serbs, all sharing the same Serbian background and language.